Back Massage and Self-Talk Therapy on Anxiety and Breastfeeding Self-Efficacy in Postpartum Mother: Analytic Descriptive - Cristinawati B/R Sihaloho; Leny Latifah; Sri Endang Pujiastuti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The delivery of the placenta makes the steroid and oxytocin hormone in the mother's body unbalanced then increases the cortisol hormone which influences the recovery and breastfeeding process. Prevalences of anxiety in the postpartum period reach to 15-40% in some countries. This was qualitative research which was explained the effect of the combination of back massage and self-talk therapies on anxiety and breastfeeding self-efficacy which these therapies are psychology therapy and physically combined. The result showed that the combination of back massage and self-talk reduced their anxiety and increased their belief to breastfeed rather than given back massage only in the control group because back massage therapy recovers their bodies and self-talk using cards as a media therapy recovers their psychology given their mind power to enjoy their postpartum period. This combination therapy effective to decrease anxiety and to increase breastfeeding self-efficacy.